2019
DOI: 10.3390/en12030489
|View full text |Cite
|
Sign up to set email alerts
|

Daylighting Performance of Solar Control Films for Hospital Buildings in a Mediterranean Climate

Abstract: One of the main retrofitting strategies in warm climates is the reduction of the effects of solar radiation. Cooling loads, and in turn, cooling consumption, can be reduced through the implementation of reflective materials such as solar control films. However, these devices may also negatively affect daylight illuminance conditions and the electric consumption of artificial lighting systems. In a hospital building, it is crucial to meet daylighting requirements as well as indoor illuminance levels and visibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
4
4
0
Order By: Relevance
“…The research findings of the present work suggest that SCFs are more effective in the presence of clear sky conditions (higher outdoor incident solar radiation levels) than of overcast sky conditions (higher outdoor diffuse solar radiation levels). This supports the fact that scientific research and promotion of these window films are more common in hot [20][21][22]24] and temperate [16][17][18]23,[25][26][27][28][29][30] climates since they present longer and more severe cooling seasons, successfully promoting the reduction in excessive solar heat gains through the windows.…”
Section: Critical Discussion and Limitationssupporting
confidence: 65%
See 3 more Smart Citations
“…The research findings of the present work suggest that SCFs are more effective in the presence of clear sky conditions (higher outdoor incident solar radiation levels) than of overcast sky conditions (higher outdoor diffuse solar radiation levels). This supports the fact that scientific research and promotion of these window films are more common in hot [20][21][22]24] and temperate [16][17][18]23,[25][26][27][28][29][30] climates since they present longer and more severe cooling seasons, successfully promoting the reduction in excessive solar heat gains through the windows.…”
Section: Critical Discussion and Limitationssupporting
confidence: 65%
“…Similarly to previous findings of research studies reported in the literature review [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], the installation of SCFs makes it possible to significantly decrease the indoor illuminance levels and temperature values due to the modification of the properties of the glazing system, with a greater emphasis for highly reflective solar control films. However, special attention should be given when choosing SCFs with application to the internal glass surface since it promotes the absorption and consequent reflection of heat towards the indoor environment, increasing the greenhouse effect of the space.…”
Section: Critical Discussion and Limitationssupporting
confidence: 64%
See 2 more Smart Citations
“…The solar control film is considered suitable for the retrofitting of the glazing system of existing buildings due to its low cost, excellent thermal insulation performance, easy installation, and minimal disruption to building occupants. , The solar spectrum selective absorption film (SSAF), a kind of solar control films, is mainly composed of transparent conductive oxides such as antimony tin oxide and indium tin oxide . It can strongly absorb solar near-infrared (NIR) radiation, and some of the absorbed energy may end up to outdoor space ultimately, reducing the transmission of solar radiation through the window. , …”
Section: Introductionmentioning
confidence: 99%